A Case of Nocardia farcinica Keratitis in a Pediatric Contact Lens Wearer. Issue 2 (March 2020) - Verner, Aimee; Durrani, Asad; Kowalski, Regis P.; Jhanji, Vishal
Abstract : Purpose: To report a case of Nocardia farcinica keratitis in a pediatric contact lens wearer. Methods: Case report and literature review. Results: A pediatric contact lens wearer was initially misdiagnosed with a poorly healing corneal abrasion after swimming with his contact lenses. On examination at our center, he was found to have a 2.5 by 2.5 mm corneal infiltrate with feathery margins. Microbiology revealed N. farcinica keratitis, which was treated with topical amikacin. The patient returned to his baseline visual acuity after treatment. Conclusions: Nocardia keratitis can be misdiagnosed because of its low prevalence, especially in young patients. Prompt diagnosis is important for proper management in these cases. The infection resolved in our patient with prompt diagnosis and treatment with topical amikacin eye drops.